The educational and scientific complex of continuing education as a new format of the new educational environment (New Collegium, 2020)
University-School clusters: Best practices and the prospects for their adaptation to Ukrainian context : the XVIII International Scientific and Practical Conference (14-th Febuary 2020, Kharkiv Univ. of Humanities “People’s Ukrainian Acad”. The article presents the author’s interpretation of the essence and social nature of the university-school cluster, the core of which, in the author’s opinion, is the system of continuing education. As exemplified by Kharkiv University of Humanities “People’s Ukrainian Academy”, one of the first educational and scientific complexes to have implemented in Ukraine the idea of continuing preparation of a person for life and work in today’s extremely fast-paced world, the author highlights the achievements of this institution during its three-decade-long existence and, most important, indicates mistakes, gaps and problems that inhibit the creation of a unified university-school cluster.